Tindak Pidana Pencurian Ringan dan Upaya Hukumnya dalam Proses Tuntutan Pemidanaan - Putri, Fresiella ‘Arsy Mahdavika; Hapsari, Iffahdah Pratama; Wardana, Dodi Jaya (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research is motivated by observational data, where crimes of petty theft are very widespread in Indonesia, how can a person be qualified as a perpetrator of a crime of petty theft, then what are the efforts of the prosecutor in dealing with criminal acts of petty theft, so that injustice does not occur like the case of Minah's grandmother, grandma asiani, grandpa samirin and many more. researcher what are the efforts of prosecutors in dealing with the crime of petty theft in order to create justice and adjust situations or conditions so that they are relevant to life in this era. then analyzed descriptively so that conclusions can be drawn.